Mengembangkan Kerajinan Perkakas Pertanian Desa Ciberem, Sumbang, Banyumas - Beny Widjarnako; Wakhudin Wakhudin; Cahyono Purbomartono (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
Agricultural tools are important for agrarian communities. However, for some people in Banyumas Regency, Central Java, very few people have businesses in the agricultural tools sector. In fact, this can be a promising business opportunity. Knowledge about making blacksmith agricultural tools is generally obtained from generation to generation. Some blacksmiths in Banyumas generally only produce agricultural tools such as kudi and work machetes, because the need for these tools never stops, is always needed by farmers or workers, and the equipment produced does not require high design, even tends to be monotonous because the main thing is its function as work equipment. That is why Science and Technology for the Community (IbM) was implemented at the Pandai Besi Kirso production house on November 6, 2025, as a method of increasing production. IbM was continued with training in techniques for selecting raw materials, making potions that can improve the quality of iron, and making a variety of new products with high quality both in terms of strength and aesthetics. It was identified that agricultural tool craftsmen generally (1) Have limitations in equipment, (2) Lack expertise in metal blending, (3) Lack of innovative product variations, not only quality but also unique ethnic ones and (4) Low management quality. The implementation of IbM is expected to be able to minimize the problems of agricultural tool craftsmen's businesses, so that the blacksmith craftsmen's community businesses can develop and have a positive impact on the existence of MSMEs in Banyumas Regency.